2020
DOI: 10.1186/s41938-020-00222-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential exploitation of Bacillus flexus biofilm against the cowpea weevil, Callosobruchus maculatus (F.) (Coleoptera: Bruchidae)

Abstract: The present study aimed to investigate new insecticidal compounds used as environmentally safe alternative to synthetic insecticides. A laboratory study was conducted to investigate the effects of Bacillus biofilms and their extracellular matrix (ECM) on the adult's mortality and reproduction of the cowpea weevil, Callosobruchus maculatus (F.) (Coleoptera: Bruchidae). Among 30 bacterial isolates, only 4 exhibited high abilities to form biofilm and showed potentials against the pest at different concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…B. acidophilus was reported as cariogenic agent by Tucker [56]. Biofilm formation by Bacillus species was reported previously [57]. Bacillus subtilis from the oral cavity was reported by Yamane et al [58].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…B. acidophilus was reported as cariogenic agent by Tucker [56]. Biofilm formation by Bacillus species was reported previously [57]. Bacillus subtilis from the oral cavity was reported by Yamane et al [58].…”
Section: Discussionmentioning
confidence: 89%
“…It was first reported by Jung et al [59] from tidal flat sediment of the Yellow Sea. Similarly, Bacillus pumilis and Bacillus flexus are the environmental microorganisms, among which the latter is known for its biofilm production [57].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, bio-concrete samples demonstrated crystalline surfaces where distinct CaCO3 crystals may recognize (Krishnapriya et al, 2015;Siddique et al, 2016;Alshalif et al, 2019). Reda et al, (2020) were reported that Bacillus flexus is the most potent one amongst the bacterial isolates that can form biofilm. Also, Rajitha et al, (2020) was noted that Bacillus haynesii produce acid-soluble extracellular biopolymer.…”
Section: Visual Observation Of Self-healingmentioning
confidence: 98%
“…On the other hand, samples of bio-concrete showed crystalline surfaces with distinct CaCO3. [56, -58].According to [59] of the bacterial isolates that can create biofilm, Bacillus flexus is the most effective. It was also reported by [60] that Bacillus haynesii produces extracellular biopolymer that is soluble in acid.…”
Section: Visual Vp-sem-edsmentioning
confidence: 99%